Kemampuan Berpikir Kreatif Siswa Pada Pembelajaran Operasi Pecahan Menggunakan Pendekatan Open-Ended - Widiastuti, Yeni; Putri, Ratu Ilma Indra (Mathematics Education Journal, 2018)
This study is descriptive research that aims to describe student’s creative thinking skills in mathematics learning with fraction topic using open-ended approach. Subject of this study is 31 students of VII-D grade of SMP Negeri 2 Inderalaya Selatan (Junior High School). The data were obtained by means of observation, test, and interviews. Written test is used in order to know level of student’s creative thinking. There is five level of student’s creative thinking skill it was very creative, creative, creative enough, less creative, not creative. The result of the research showed that from 31 students, 3% student was very creative, 48% students was creative, 29% students was creative enough, 10% students was less creative, and 10% students was not creative. It could be concluded that students of VII-D grade of SMP Negeri 2 Inderalaya Selatan was creative enough.